Encouraging Students' Vocabulary Mastery Using English Cartoon Films as Media at SMP Negeri 6 Satap Kawangkoan - Walangitan, Estrelita Kristina; Pelenkahu, Noldy; Rorimpandey, Rinny S (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study explores the potential of English cartoon films as an educational tool to enhance vocabulary mastery among seventh-grade students at SMP Negeri 6 Satap Kawangkoan. The research addresses common issues in language learning, such as difficulty in understanding reading texts, limited vocabulary, and lack of student engagement in learning English. Employing a quantitative research design with a pre-test and post-test structure, the study measures the impact of English cartoon films, particularly We Bare Bears: Burrito, on students’ vocabulary mastery. The results indicate that cartoon films are an effective medium for teaching English vocabulary, as evidenced by a significant increase in student scores between the pre-test (70.71) and post-test (91.71). Observations further demonstrate that the use of cartoons makes learning more enjoyable, interactive, and engaging for students, fostering greater enthusiasm and active participation in the classroom. These findings suggest that integrating cartoons as media can be a valuable strategy for improving English vocabulary skills among young learners.